A framework for reducing water demand in multi-storey and detached dwellings in the United Arab Emirates. - Shanableh, A.; Imteaz, M.; Merabtene, T.; Ahsan, A. (2012)
The United Arab Emirates (UAE) is highly dependent on desalination for water supply in urban areas, which comes at significant financial and environmental costs. Therefore, reducing the demand for water is a strategic objective of water authorities in the UAE. The concentration of the UAE population in multi-story buildings in urban areas makes residential water conservation, including greywater recycling, a highly attractive option for reducing water demand and wastewater generation. However, the unique composition of the UAE population poses challenge to adopting water conservation policies that are suitable for the UAE national and expatriate sectors of the population. Furthermore, the current water recycling policies and legal framework do not encourage greywater recycling for internal use in residential buildings. In this study, a framework for assessing the potential and feasibility of water conservation, including greywater recycling, in multi-storey and detached dwellings in the UAE was developed and discussed. The results confirmed that significant potential existed for reducing the residential water demand in the UAE through adopting simple water conservation measures and greywater recycling in multi-story buildings. The discussion was extended to proposing greywater recycling systems suitable for multi-story buildings in the UAE. Such systems involve partial greywater recycling from the higher floors of multi-storey buildings to serve the toilet flushing needs of the whole building and locating greywater treatment systems on the roofs of buildings.